Emerging Trends of Nanotechnology in Cancer Therapy - Reddy, A.Kishore (International Journal of Pharmaceutical & Biological Archive, 2011)
Cancer is a malignant disease caused by damage of genes that control growth and division of cells and it is complex as it entails multiple cellular physiologic systems such as cell signaling and apoptosis .it is being missed at its earliest stages because of detection methods that are not directed at cellular changes of carcinogenesis .Non specific systemic distribution , inadequate drug concentrations reaching tumor , inability to monitor therapeutic responses continue to plague the area of clinical oncology . Nanotechnology has the potential to offer solution to these current obstacles in cancer therapy because of its unique size (1-100nm) and large surface-to-volume ratios .The versatility of the nanotechnology platform could allow cellular tracking using single or multimodal imaging modalities. Nanoparticles are being used to detect biomarkers which may help researchers with molecular imaging of malignant lesions and allow physicians to see cells and molecules undetectable through conventional imaging. Additionally photo luminescent nanoparticles may allow oncologists to discriminate cancerous and healthy cells. Clinical investigations suggest that therapeutic nanoparticles can improve patient care and quality of life by reducing off-target toxicities by more selectively directing drug molecules to intracellular targets of cancer cells.